(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Reproductive dysfunction following insulin deficiency in Diabetes Mellitus has been well reported among diabetic patients. However, the mechanism through which Diabetes alters reproductive function remains oblivion. While most studies have focused on diabetes mellitus in male subjects, there have been cases on altered reproductive functions in females. These present study aims to investigate the effect of long term hyperglycemia on diabetic rats’ ovary. Female Wistar rats were assigned into control and diabetic group, each consisting of five animals. The later was induced with STZ (50mg/Kg intraperitoneal injection) and the animals were sacrificed after 14 weeks. The blood glucose, body and organ weight, serum hormone level along with oxidative stress parameters of the ovary and uterus were determined. Histology of the ovary and expression levels of CD79 in the ovary was also assessed. The weight of the diabetic rats after the experiment was significantly lower (p<0.05) than the control. The level of Follicle Stimulating Hormone, Luteinizing hormone and estrogen was significantly lower in the diabetic group. The antioxidant enzymes catalase, superoxide dismutase (SOD) and glutathione-s-transferase (GST) were significantly lower in the diabetic ovary and uterus while the Malondialdehyde (MDA) concentration significantly increased compared to the control group. Histological observation of the ovary showed signs of chronic inflammation and immunohistochemistry for CD79 showed positive expression in the diabetic ovary. Our research findings suggest that Diabetes mellitus alters ovarian health by altering hormonal balance and stimulating oxidative damage